Evaluation of Osseointegration and Bone Healing Using Pure-Phase β - TCP Ceramic Implant in Bone Critical Defects. A Systematic Review - Garcia, Daniel Cardoso; Mingrone, Larissa Eckmann; Sá, Marcelo Jorge Cavalcanti de (Frontiers in Veterinary Science, 2022)
Background: The gold standard for osseointegration remains the autogenous bone graft, but biomaterials such as β - TCP in its pure-phase showed promising results to be practical bone substitutes. This kind of implants are optimal candidates for bone integration due to their osseoconductive, biocompatibility, bioactivity, and absorptive properties. Methods: A systematic review was conducted using 5 databases for searching published studies between January 1st 2011 and June 15th 2021. Only clinical and experimental studies, and case reports were included in this research. Human and animal studies published only in Portuguese or English with clinical, radiologic, and histologic evidence of new bone formation, osseoconduction and osseointegration were included. This systematic review was reported according to PRISMA guidelines. Results: Approximately 14.500 articles were initially found, but after advanced searching using specific including and excluding keywords, matching Boolean operators “AND”, “OR” and “NOT”, and after excluding duplicates, a total of 11 articles were included for this systematic review, including experimental works, a retrospective study, a randomized controlled clinical study, a randomized prospective study, a prospective observational study, and a case report. All articles showed 100% effectiveness in bone integration after β - TCP implantation by clinical, radiological and/or histologic assessment. Implant shape and porosity seem to have influence in osseointegration process. β - TCP can give predictable, sustainable, and adequate new bone formation with the least infection rates in implant placement cases and patient morbidity, which is the current goals for bone integration, augmentation and replacement. Conclusion: More clinical studies in the future, demonstrating specific metric measurements in relation to bone consolidation, as well as showing results with other shapes of this implant are needed to evaluate further in depth osseoconductive and osseointegrative characteristics of this biomaterial, in order to develop new comparisons and quantitative analyses. β - TCP is widely used in dentistry and there is a lack of information about the use of this biomaterial for filling critical segmental defects of long bones in veterinary medicine, but only in small defects and in experimental studies, with no clinical cases performed in animals with a longer observation time.